2005
DOI: 10.2320/matertrans.46.228
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Hydroxyapatite Thin Films on Titanium Substrates Prepared by Ultrasonic Spray Pyrolysis

Abstract: Calciumhydroxyapatite thin films have been prepared by ultrasonic spray pyrolysis deposition on titanium substrate. The surface morphologies of the films formed at different deposition times were analysed by using SEM. The mechanism of the films formation was investigated in relation to the observed film morphology during the first stages of its formation, as well as to its consolidation to the final form. The chemical homogeneity of the synthesized films was determined by using EDS analysis, whereas the phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The FT-IR spectrum of the HAp produced by hydrothermal method shown in Fig.4 shows all the characteristic bands for Hydroxyapatite [14,15]. The asymmetric stretching (v 3 ) and bending (v 4 ) modes of PO 4 -3 ion were detected at around 1047.9, and 604.1 and 566.7 cm were also present [16].…”
Section: Resultsmentioning
confidence: 99%
“…The FT-IR spectrum of the HAp produced by hydrothermal method shown in Fig.4 shows all the characteristic bands for Hydroxyapatite [14,15]. The asymmetric stretching (v 3 ) and bending (v 4 ) modes of PO 4 -3 ion were detected at around 1047.9, and 604.1 and 566.7 cm were also present [16].…”
Section: Resultsmentioning
confidence: 99%
“…The waves formed by transferring ultrasound oscillations on a given precursor, depending on the superposition conditions, have a complex spatial form that primarily depend on oscillation damping factors in different directions (in the direction parallel or perpendicular to the direction of deformation) and on the forced frequency of the ultrasonic generator [15][16][17][18][19][20][21][22][23][24][25]. Based on the 3D model of capillary standing waves, formed at the meniscus surface, the following expression is obtained:…”
Section: Particle Levelmentioning
confidence: 99%
“…The particle size distribution can be estimated by equation [15][16][17][18][19][20][21][22][23][24][25]:…”
Section: Particle Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…The most commonly used metallic implants are based on titanium and its alloys due to their excellent mechanical properties and corrosion stability [16]. Unfortunately, studies in the ield showed that bare titanium or other metallic implants can determine ion release into body [17].…”
Section: Biomaterialsmentioning
confidence: 99%